Language-Independent Text-Line Extraction Algorithm for Handwritten Documents - Ryu, Jewoong; Koo, Hyung Il; Cho, Nam Ik (IEEE signal processing letters, 2014)
Text-line extraction in handwritten documents is an important step for document image understanding, and a number of algorithms have been proposed to address this problem. However, most of them exploit features of specific languages and work only for a given language. In order to overcome this limitation, we develop a language-independent text-line extraction algorithm. Our method is based on connected components (CCs), however, unlike conventional methods, we analyze strokes and partition under-segmented CCs into normalized ones. Due to this normalization, the proposed method is able to estimate the states of CCs for a range of different languages and writing styles. From the estimated states, we build a cost function whose minimization yields text-lines. Experimental results show that the proposed method yields the state-of-the-art performance on Latin-based and Chinese script databases. Further, we submitted the proposed algorithm to the ICDAR 2013 handwriting segmentation competition and our method showed the best text-line extraction performance among 10 participant methods.